Vegetable oils as monomeric and polymeric materials: A graphical review - Gaglieri, Caroline [UNESP]; Alarcon, Rafael T.; de Moura, Aniele [UNESP]; Bannach, Gilbert [UNESP] (Elsevier, 2022)
Vegetable oils have been extensively researched, and many reviews have been published about them. However, most of them are focused on soybean and linseed oils and reactions, such as epoxidation, but do not take into account other potential sources or reactions that can provide high value products. Therefore, the present work aims to cover these overlooked topics illustrating different sources of vegetable oils including baru, macaw, andiroba, grape, passion fruits, neem, and so on. Furthermore, some chemical modifications and their resulting monomers are discussed, for instance, maleinization, epoxidation, acrylation, carbonatation, and click chemistry, and forth. Consequently, there are several ways to use vegetable oils to produce renewable polymers for use in technological fields, such as photopolymerisation and vitrimers. The latter has received great attention in recent research due to their recovering, reshaping, and welding properties.
Keywords: Biomass valorisation; Green chemistry; Renewable polymers; Vitrimers